MULTIVARIATE STATISTICAL METHODS IN DETERMINING THE SPATIAL DISTRIBUTION OF CHEMICAL ELEMENTS IN SOILS (KUMANOVO REGION, NORTH MACEDONIA) (Geologica Macedonica, 2023)
The results of the distribution of various chemical elements in soil samples from the region of Kumanovo, North Macedonia, are presented. In order to determine the occurrence of chemical elements, soil samples were collected from a total of 51 locations. At each location, soil samples were collected from two layers, topsoil (0–5 cm) and subsoil (20–30 cm), in an area of 5×5 km2. The soil samples were analyzed for 5 elements using two instru-mental methods: inductively coupled plasma – atomic emission spectrometry (ICP-AES) for 17 macroelements (Al, B, Ba, Ca, Cr, Cu, Fe, K, Li, Mg, Mn, Na, Ni, P, Pb, V, and Zn) and inductively coupled plasma – mass spectrometry (ICP-MS) for 38 trace elements (Ag, As, Be, Bi, Br, Cd, Ce, Co, Cs, Dy, Er, Eu, Ga, Gd, Ge, Hf, Ho, In, La, Lu, Mo, Nb, Nd, Pr, Rb, Sb, Sc, Sm, Sn, Sr, Ta, Tb, Ti, Tm, W, Y, Yb, and Zr). Factor analysis was applied to analyze the factors affecting the linear combination variables grouped under the same factor. Spatial distribution maps for each factor as well as distribution maps for the analyzed elements were obtained by universal kriging interpolation. It was found that the distribution of most elements follows the lithology of the studied area, except for some elements (As, Pb, and Zn) whose higher contents were found in some specific parts of sub-areas, which is due to the current and past mining activities in the region.
Keywords: soil pollution; potentially toxic elements; Kumanovo region; North Macedonia